The Effect of Providing Nitrogen on The Growth of Kesum (Persicaria minor Huds.) in a Deep Water Culture Hydroponic System - Sandy Ramadani; Wan Arfiani Barus; Yaseer Suhaimi bin Mohd (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2026)
Kesum (Persicaria minor Huds.), a plant rich in flavonoids such as quercetin and quercetin-3-glucuronide, holds significant value as a traditional medicine and distinctive culinary herb, particularly in West Kalimantan. This study evaluated the effects of five nitrogen concentrations (0, 50, 100, 150, and 200 mg L⁻¹) on the growth and phytochemical accumulation of kesum cultivated using a floating-raft deep water culture (DWC) hydroponic system. The experiment was conducted in a greenhouse at MARDI, Malaysia, employing a randomized block design with five replications. The results revealed highly significant effects of nitrogen (p < 0.01) on all measured growth and phytochemical parameters. Key findings include the highest plant height (80.33 cm) at 100 mg L⁻¹ nitrogen, maximum biomass production (fresh weight 176.64 g and dry weight 43.99 g per 30 plants) at 150 mg L⁻¹ nitrogen, and a substantial increase in phytochemical content at 50 mg L⁻¹ nitrogen, with quercetin-3-glucuronide reaching 98 µg/mg and quercetin 67 µg/mg—2 to 3 times higher than the control. In contrast, 200 mg L⁻¹ nitrogen caused toxicity, resulting in reduced biomass and phytochemical levels. Based on these findings, the optimal nutrient recommendations are 100–150 mg L⁻¹ nitrogen (with phosphorus maintained at 150 mg L⁻¹ and potassium at 200 mg L⁻¹) for commercial production aimed at maximizing fresh leaf yield and biomass, and 50 mg L⁻¹ nitrogen for cultivation focused on maximizing bioactive compound content for phytochemical extraction and the phytopharmaceutical industry.